Increase of collagen in diabetes-related traumatic ulcers after the application of liquid smoke coconut shell - Meircurius Dwi Condro Surboyo; Ira Arundina; Retno Pudji Rahayu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Traumatic ulcers in patients with diabetes mellitus may experience delayed healing despite their diabetic condition being controlled. Liquid smoke coconut shell containing phenolic compounds can potentially accelerate the healing process. One healing process indicator is the increased number of fibroblasts, another being the increased amount of collagen. Purpose: This study aimed to analyze the amount of collagen in traumatic ulcers in diabetics after application of liquid smoke coconut shell. Methods: Alloxan was induced in twenty-four male Wistar rats as models of diabetes mellitus. A traumatic 10 mm ulcer was made along the labial fornix incisive inferior with a round, stainless steel blade before liquid smoke coconut shell and benzydamine hydrochloride (as the control) was administrated once a day. A biopsy of the labial fornix incisive inferior was subsequently performed after the topical application for 5 and 7 days. Histological assessment was conducted to analyze the amount of collagen by means of Masson Trichome staining. Results: Histologically, the topical application of liquid smoke coconut shell for 5 days significantly increased the amount of collagen, higher than that of benzydamine hydrochloride as the control (p=0.006) (p<0.05). Meanwhile, the topical application of liquid smoke coconut shell for 7 days made the concentration of collagen no significantly different from that of benzydamine hydrochloride as the control (p=0.156) (p>0.05). Conclusion: Liquid smoke coconut shell applied for 5 days increase the amount of collagen in traumatic ulcers in diabetic patients.